Recovering full metallic resources from waste printed circuit boards: A refined review. (20th January 2020) - Qiu, Ruijun; Lin, Mi; Ruan, Jujun; Fu, Yonggao; Hu, Jiaqi; Deng, Meiling; Tang, Yetao; Qiu, Rongliang
Abstract: Huge environment stresses and economic benefits promoted the vigorous development of recovery technology of waste printed circuit boards. However, the recovery technologies of metals from waste printed circuit boards were lack of systematicness, definiteness, and full-value. In this paper, we have systematically reviewed the literature, compared the advantages and limitations of various recycling methods, and established a complete framework for recycling waste printed circuit boards (PCBs). Then, an integrated, definite, and systematic recovery route of full renewable metals from waste printed circuit board was proposed. The recovery route included temperature-control crushing, magnetic separation, high voltage electrostatic separation, vacuum gasification and condensation, electrolysis, and bioleaching. This will raise people's attention to recycling in an environment-friendly, energy-saving and value-added way, providing new ideas and entry points for future e-waste recycling. Finally, the perspective of the recovery route of full metals from waste printed circuit boards were looked forward. This review will contribute to the industrialization of metallic resources recycle and energy saving.